SOCIAL SENSITIVITY OF STUDENTS OF DARUL FAQIH ISLAMIC BOARDING SCHOOL MALANG TOWARDS COMMUNITY-BASED LEARNING METHODS - Siti Ainun Hafidzoh; Edi Widianto (IKIP Siliwangi Bandung, 2022)
Community-based learning, especially social, is the most important thing to be implemented. Therefore, the researcher aims to describe community-based learning, describe social students, and find out the influence of community-based learning methods by utilizing social students at Darul Faqih Islamic Boarding School Malang. This study uses a quantitative method with a sampling technique that is a saturated sample of 80 students of the Darul Faqih Islamic boarding school Malang. The data analysis technique used is a simple linear regression analysis technique by considering the classical assumption test consisting of residual normality, linearity, and heteroscedasticity tests. The results showed that (a) the community-based learning method carried out by students was in a good category, which was 91.1%, (b) the social potential of students was in a good category, which was 94.9%, (c) there was an influence of community-based learning on the social location of the students of Darul Faqih Malang with a value of sig. 1.256 > 1.994, meaning that community-based learning affects the places available for students. In the future, community-based learning in Darul Faqih Islamic Boarding School will further develop intelligence and skills in society. For Darul Faqih students, it is recommended to better understand community-based learning and be patient to provide facilities and social care so that they can practice when they leave the Islamic boarding school.